Rabbitfish Behavior Against Different Light Colors and Light Intensities - Himam, M. Iqbal; Puji Rejeki, Sri Untari; Darmawan, Darmawan; Nazaruddin, Nazaruddin; Marjoni, Marjoni; Nasruddin, Nasruddin; Nurlaela, Eli (Politeknik Kelautan dan Perikanan Dumai, 2024)
Abstract